2020
DOI: 10.3390/nano10081464
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Methyl Orange Uptake by Mn–Rich Synthetic Mica: Insights into Manganese Role in Adsorption and Selectivity

Abstract: Manganese–containing mica (Mn–mica) was synthesized at 200 °C/96 h using Mn–carbonate, Al–nitrate, silicic acid, and high KOH concentration under hydrothermal conditions. Mn–mica was characterized and tested as a new adsorbent for the removal of methyl orange (MO) dye from aqueous solutions. Compared to naturally occurring mica, the Mn–mica with manganese in the octahedral sheet resulted in enhanced MO uptake by four times at pH 3.0 and 25 °C. The pseudo–second order equation for kinetics and Freundlich equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…q max (mg/g) References Amino-crosslinked hypromellose (AHM) 15.56 [34] Blast furnace slag acid-alkali precipitate (BFSAP) 167 [94] Protonated cross-linked chitosan 180.2 [95] Coffee ground activated carbon 658 [96] Waste ash 35.614 [36] Chitosan-coated montmorillonite clay 7.34 [97] Alkali-Activated Polypyrrole-Based Graphene Oxide 520.8 [98] Manganese-containing mica (Mn-mica) 107.3 [35] PANI NFs 312.8 Present study of MO ions within the column bed in higher bed lengths may result in the observed bed capacity upsurge, hence larger volumes of MO solution could be treated. Presented in Table 3 are the values of the amount of solution treated at breakthrough point, (V b ) which were found to be 8.64 L, 17.64 L, and 29.16 L for bed lengths of 3, 5.5, and 9 cm, respectively.…”
Section: Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…q max (mg/g) References Amino-crosslinked hypromellose (AHM) 15.56 [34] Blast furnace slag acid-alkali precipitate (BFSAP) 167 [94] Protonated cross-linked chitosan 180.2 [95] Coffee ground activated carbon 658 [96] Waste ash 35.614 [36] Chitosan-coated montmorillonite clay 7.34 [97] Alkali-Activated Polypyrrole-Based Graphene Oxide 520.8 [98] Manganese-containing mica (Mn-mica) 107.3 [35] PANI NFs 312.8 Present study of MO ions within the column bed in higher bed lengths may result in the observed bed capacity upsurge, hence larger volumes of MO solution could be treated. Presented in Table 3 are the values of the amount of solution treated at breakthrough point, (V b ) which were found to be 8.64 L, 17.64 L, and 29.16 L for bed lengths of 3, 5.5, and 9 cm, respectively.…”
Section: Adsorbentmentioning
confidence: 99%
“…To date, multiple natural and artificial sorbents have been employed for MO remediation from wastewater. These include polypyrrole nanofibers [ 28 ], activated carbon [ 30 ], modified coffee waste [ 31 ], chitosan hydrogel beads [ 32 ], magnetic iron oxide/carbon nanocomposite [ 33 ], amino-crosslinked hypromellose [ 34 ], bentonite and coffee grounds activated [ 34 , 35 ], waste ash [ 36 ], populous tree leaves [ 37 ], manganese-rich synthetic mica [ 35 ], etc . However, all of these adsorbents were explored in batch adsorption mode, which is well acknowledged to provide insufficient information for scaling up [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the point of zero charge (pH PZC ) was determined as follows [9]: 50 mL of 0.1 M KCl was taken in a clean glass Erlenmeyer. The initial pHs (pHi) of these solutions were adjusted at pH values ranging from 2.0 to 10.0.…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
“…The appropriateness of these advanced models to fit MB and MO adsorption data was compared, and the best one was identified according to the determined coefficient R 2 values [13]. These advanced models are described as follows [9,13,31]:…”
Section: Mb and Mo Adsorption Modelingmentioning
confidence: 99%
See 1 more Smart Citation